Whole-Exome Sequencing Identifies a Novel CPT2 Mutation in a Pedigree With Gout - Guo, Yong; Jin, Jing; Zhou, Zhenni; Chen, Yihui; Sun, Li; Zhang, Chunwu; Xia, Xiaoru (Frontiers in Cell and Developmental Biology, 2022)
Background Gout is a common inflammatory arthritis, and its exact pathogenesis remains unclear. Multiple studies have demonstrated the genetic factors play important roles in the development of gout. This study aims to investigate the genetic basis in a three-generation pedigree with gout. Methods Whole-exome sequencing (WES), comprehensive variant analyses and co-segregation testing were performed. Effects of candidate variants on protein localization and expression in cells, and interaction with gout-related genes were then conducted. Results After comprehensively bioinformatics analysis, Sanger sequencing validation and co-segregation analysis in the pedigree, we identified a rare heterozygous missense variant (c.1891C>T, p.R631C) in CPT2. Although no change of localization was observed, the results showed that the ﬂuorescence intensity of p.R631C mutants was obviously reduced than wild-type protein, suggesting that protein degradation caused by the mutant. Furthermore, our results also indicated that the c.1891C>T variant influence the binding ability of CPT2 with UCP2. Conclusion This study identifies a rare mutation in CPT2 in a large Chinese pedigree with gout. Functional studies indicate the effect of this mutant. This study provides novel insight into the genetic aetiology of gout.